Uromodulin: from monogenic to multifactorial diseases. Issue 8 (16th September 2014) - Scolari, Francesco; Izzi, Claudia; Ghiggeri, Gian Marco
Abstract : Uromodulin, the major protein secreted in normal urine, is exclusively produced in the thick ascending limb (TAL) cells of the kidney. The exact role uromodulin (UMOD) plays in renal physiology remains enigmatic. UMOD has been linked to water/electrolyte balance and to kidney innate immunity and it is believed to protect against urinary tract infections and renal stones. A renewed interest in UMOD has been triggered by the identification of UMOD mutations as cause of hereditary dominant renal diseases, now referred to as uromodulin-associated kidney diseases (UAKDs), presenting with tubulointerstitial fibrosis, defective urinary concentration, hyperuricaemia and gout, and progressive renal failure. In UAKDs, the key primary pathogenetic event is a delayed intracellular trafficking of mutant UMOD, causing its intracellular accumulation. In the last decade, multiple genome-wide association studies have identified common variants in the UMOD gene, causing independent susceptibility to chronic kidney disease (CKD) and hypertension, two complex traits representing major global health problems. The biological mechanism underlying the association between UMOD risk variants and susceptibility to CKD and hypertension was not understood until last year, when the link between UMOD and hypertension was found to be caused by overactivation of the TAL sodium–potassium–chloride co-transporter NKCC2, pointing to UMOD as a therapeutic target for lowering blood pressure and preserving renal function.